MAKNA SIMBOLIK KOMUNIKASI BUDAYA DALAM UPACARA ADAT PERKAWINAN MASYARAKAT BATAK TOBA DI PEKANBARU - Vivi Aprilia; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Batak Toba traditional wedding ceremony is one of the unique cultural heritagevalues are present and thrive in the city of Pekanbaru. In a traditional wedding ceremonyBatak Toba there are aspects that are rich in symbolic meaning of the represented physicalobjects and food and speech. The aim of the study is to determine the meaning of thesymbolic situation, meaning the product of social interaction and meaning interpretation ofthe traditional wedding ceremony Batak Toba in Pekanbaru.This study used qualitative methods to approach symbolic interaction. Informants inthis study is parhata / protocols that exist on Batak Toba traditional wedding ceremony inSingapore as well as parents and guests who were there at the marriage ceremonies.Techniques of data collection is done through observation, interview, and documentation.The results showed that the situation of symbolic meaning in traditional weddingceremony Batak Toba in Pekanbaru consist of physical objects includes ihan (fish), mandarhela (gloves groom), Ulos (shawl) and Boras (rice) and boli / tuhor ( dowry) while the socialobject traditional wedding ceremony is a form of verbal behavior interactions that occurbetween the family that marhusip, marhata sinamot and martonggo king. Meaning theproducts of social interaction in a traditional wedding ceremony in the form of the meaningof marriage ceremonies both in terms of the bride and groom, parents of the bride, parhataand invited guests. Both bride and groom parents interpret the traditional weddingceremony of cultural, ritual and sacred very high. Parhata / protocol to interpretthetraditional wedding ceremony has a value of solidarity (assimilation), cultural, spiritualand sacred. While the audience to interpret the traditional wedding ceremony has culturaland spiritual values. Interpretation of the meaning of marriage ceremonies in the form of theaction covered and open action. Measures covered include the bride and groom internalmotivation (self), external motivation (encouragement of family and friends), as well asfeeling happy and proud to be a bride for being able to carry out the traditional weddingceremony. Opening acts include facial expressions both families who have moved and happygaze that became the embodiment of fun and seriousness of the bride and groom in the holdand preserve their culture Batak Toba traditional wedding ceremony.